Mengungkap Peran Strategis Sukuk dan Saham Syariah dalam Mendorong Pertumbuhan Keuangan Syariah di Era Modern - Syarif, Dafiar; Wahyu, Wawan Devis; Sarmigi, Elex; Rahman, Paisal (Universitas Islam Raden Rahmat, 2025)
This study examines the impact of sukuk and Islamic stocks on the development of Islamic finance in Indonesia during the period 2015–2023. The main focus of this research is to understand the strategic role of these two Islamic capital market instruments in driving the growth of the Islamic finance sector, which includes banking, insurance, and Islamic microfinance institutions. The methodology used is quantitative analysis with a Structural Equation Modelling - Partial Least Squares (SEM-PLS) approach. The results show that Islamic sukuk has a positive and significant impact on the performance of Islamic finance, with a path coefficient of 0.846 and a p-value < 0.05, while Islamic stocks show a weak and insignificant relationship with the performance of Islamic finance, with a path coefficient of 0.195 and a p-value > 0.05. These findings indicate that Islamic sukuk plays a more dominant role in supporting the growth of the Islamic finance sector in Indonesia, while Islamic stocks require further development, including increasing financial literacy and public interest in these instruments. This study contributes theoretically by expanding the literature on Islamic finance and practically by providing recommendations for regulators to strengthen the role of Islamic sukuk in supporting sustainable Islamic finance in Indonesia.